An Update Review on the Paneth Cell as Key to Ileal Crohn's Disease - Wehkamp, Jan; Stange, Eduard F. (Frontiers in Immunology, 2020)
The Paneth cells reside in the small intestine at the bottom of the crypts of Lieberkühn, intermingled with stem cells, and provide a niche for their neighbors by secreting growth and Wnt-factors as well as different antimicrobial peptides including defensins, lysozyme and others. The most abundant are the human Paneth cell -defensin 5 and 6 that keep the crypt sterile and control the local microbiome. In ileal Crohn´s disease various mechanisms including established genetic risk factors contribute to defects in the production and ordered secretion of these peptides. In addition, life-style risk factors for Crohn´s disease like tobacco smoking also impact on Paneth cell function. Taken together, current evidence suggest that defective Paneth cells may play the key role in initiating inflammation in ileal, and maybe ileocecal, Crohn´s disease by allowing bacterial attachment and invasion.